The Cauchy integral formula for (p, q)-monogenic functions with α-weight in superspace - Gao, Long; Du, Xiaojing; Liang, Xiaotong; Xie, Yonghong (Complex variables and elliptic equations, 2025)
First, some properties for $ (p,q) $ ( p , q ) -monogenic functions with α-weight in superspace are obtained. Then the Cauchy-Pompeiu formula in superspace is given. Finally, the Cauchy integral formula and the Cauchy integral theorem for $ (p,q) $ ( p , q ) -monogenic functions with α-weight in superspace are proved.